Microscale organic laboratory with multistep and multiscale syntheses - Mayo, Dana W.; Pike, Ronald M.; Forbes, David C. (Hoboken, NJ John Wiley & Sons, Inc., 2023)
When Microscale Organic Laboratory (MOL) was first published in 1985 as paperback Xerox copies of an unproofed manuscript, it was the only microscale organic laboratory text available. In the February 1999 Book Buyers Guide Supplement to the Journal of Chemical Education, however, there were seventeen laboratory manuals (of a total of thirty-nine) containing miniaturized, fully microscale, or a mixture of micro and macro experiments. Fast forward a decade and a half and without any doubt, microscale techniques have solidly established their place in chemical education. The number of lab manuals currently in print reflects the growing number of students being introduced to organic chemistry through microscale techniques. While the conversion may not yet be quite as high as the eighty percent predicted by David Brooks back in 1985, a conservative estimate would be that a solid two-thirds majority of sophomore students now work with miniaturized experiments compared with the amounts of material employed in these laboratories in the late 1970s"-- Provided by publisher.
Includes index.
Keywords: Chemistry, Organic -- Laboratory manuals